Partial recovery of macro-epibenthic assemblages on the north-west shelf of the Black Sea. - Stevens, Tim; Mee, Laurence; Friedrich, Jana; Aleynik, Dmitry; Minicheva, Galina (PANGAEA, 2019)
The dataset contains information about density (ind.m2) and percent cover of epibenthic organisms on the north-western shelf of the black sea, sampled in summer 2006 and spring 2008. Data are derived from video tows at 29 and 36 stations, respectively, at depths from 13 to 122m. Data is in the form of excel files with 2 sheets, one for each year. Each sheet contains co-ordinates and station names.
Epibenthos of the North-western Shelf of the Black Sea
Keywords: Epibenthos Black Sea